Self-renewal of CD133hi cells by IL6/Notch3 signalling regulates endocrine resistance in metastatic breast cancer - Pasquale Sansone (Nature Portfolio, 2016)
ER+ breast cancer patients treated with endocrine therapies often acquire resistance and develop metastasis. In this study, the authors demonstrate that endocrine therapies can promote the self-renewal of CD133hi/ERlodrug resistant cells with metastatic potential driven through the IL6-Notch3 axis activation.